Method for preparing concrete road components using a new type of red mud-based aggregate
Patent Information
- Application Number
- CN202410358246.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-27
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-03-27
AI Technical Summary
然而,该技术在赤泥基胶凝材料制备中,依旧采用了煅烧制备,难以避免制备中所带来了一系列环境及能耗污染问题,且其为了提高赤泥基轻骨料/轻骨料混凝土性的强度,在赤泥基胶凝材料基础上,增加利用了发泡剂、有机硅防水剂、地聚物胶结材料等
[0044]1. The solid waste-based cementitious material prepared in this invention utilizes the synergistic and mechanical activation effects of a rationally proportioned mixture of solid wastes such as red mud, desulfurized gypsum, fly ash, and slag powder to form hydraulic cementitious properties. Its mineral composition is similar to that of rapid-hardening sulfoaluminate cement, exhibiting excellent characteristics such as rapid hardening, early strength, and high strength. It can compensate for the shortcomings of ordinary silicate cement, significantly shorten the setting time, and improve the production efficiency of subsequent concrete component preparation. The preparation process does not require calcination, realizing the practical application value of large-scale industrial solid waste disposal, reducing environmental pollution and safety hazards.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of building material recycling technology, and in particular to a method for preparing concrete road components using a novel red mud-based aggregate. Background Technology
[0002] With the rapid development of infrastructure construction, the demand for curb stones, slope protection components, drainage components, and paving bricks, as important components of road structures, is increasing rapidly. Concrete road components not only serve functions such as warning, drainage, and slope protection, but also contribute to the stability of the roadbed and pavement. Their performance is directly related to the smooth flow and safe operation of highways.
[0003] In terms of existing lightweight aggregate concrete preparation technology, most of them use natural lightweight aggregates such as natural crushed stone and sand. However, the mining volume of such natural aggregates is limited and the cost is gradually increasing. Therefore, people are preparing red mud-based lightweight aggregates to replace natural lightweight aggregates and solve the problems of insufficient resources and high costs, while realizing the comprehensive utilization of red mud solid waste. However, existing processing technologies for red mud-based lightweight aggregates generally employ sintered red mud aggregates, and the amount used has been gradually increased to achieve full utilization of red mud. However, in practical applications, it has been found that red mud contains a large amount of alkaline substances that are prone to precipitation, causing efflorescence on the material surface. Furthermore, the chemical composition of red mud is mainly Al2O3, SiO2, and Fe2O3, while its mineral composition includes hydrated calcium zeolite, nepheline, calcite, illite, hydrated sodium aluminosilicate, and hematite, resulting in low cementitious activity. When the amount of red mud in the cementitious material is high, the inherent characteristics of red mud also increase the impact on product performance, hindering strength formation and leading to insufficient material strength. This necessitates other remedial measures, increasing process complexity and making it difficult to achieve the desired efficiency in the actual application of red mud. Therefore, there is still room for technological research and development in a comprehensive utilization technology for red mud solid waste with appropriate dosage and sustainability, compared to simply increasing its proportion in existing technology products.
[0004] Patent No. 202011603760 3, entitled "Red Mud-Based Cementitious Materials, Red Mud-Based Lightweight Aggregates, Red Mud-Based Lightweight Aggregate Concrete and Their Preparation Methods," addresses the problems of low red mud utilization and the existing sintering method primarily used in lightweight aggregate concrete preparation. It improves upon these methods by preparing red mud-based cementitious materials, mixing and grinding them with fly ash and red mud, granulating, and curing them to prepare red mud-based lightweight aggregates, and then further preparing red mud-based lightweight aggregate concrete. However, this technology still employs calcination in the preparation of the red mud-based cementitious materials, which inevitably leads to a series of environmental and energy pollution problems. Furthermore, to improve the strength of the red mud-based lightweight aggregate / lightweight aggregate concrete, it adds foaming agents, organosilicon waterproofing agents, and geopolymer binders to the red mud-based cementitious materials. In addition, to achieve multi-stage iteration and comprehensive utilization of red mud, the process uses a relatively high amount of red mud. As for this type of product used in the preparation of concrete components, the quality problems caused by efflorescence are difficult to eliminate.
[0005] To enhance the practical application value and comprehensive utilization of red mud-based lightweight aggregates and reduce environmental burden, this application explores more practical and effective technical measures. In the manufacturing process of products using red mud, the red mud content is rationally controlled. Furthermore, red mud-based cementitious materials and novel red mud-based lightweight aggregates are prepared using solid waste without sintering and applied to engineering construction. This process is entirely non-firing, ensuring the strength of red mud-based lightweight aggregates while addressing the drawbacks of ore resource shortages, severe energy consumption and pollution, and complex production processes. It improves the production efficiency and performance of concrete components, contributing to sustainable development through energy conservation and emission reduction, and has significant practical implications. Summary of the Invention
[0006] This invention provides a method for preparing concrete road components using a novel red mud-based aggregate. The method involves preparing concrete road components using a solid waste-based rapid-hardening cementitious material and red mud-based lightweight aggregate. All processes are non-sintering, ensuring the strength of the red mud-based lightweight aggregate and resulting in high-performance concrete road components, thus solving the problems existing in the prior art.
[0007] The technical solution adopted in this invention is:
[0008] A method for preparing concrete road components using a novel red mud-based aggregate includes the following steps:
[0009] (1) Preparation of solid waste-based rapid hardening cementitious materials
[0010] Red mud, gypsum, fly ash, slag powder and high-efficiency binder are added in a weight ratio of 5-15:10-20:15-25:20-30:25-35 and mixed by ball milling.
[0011] (2) Preparation of red mud-based lightweight aggregate
[0012] Red mud, solid waste-based rapid-hardening cementitious material, steel slag, coal gangue, and binder aqueous solution are fed into the mixture at a weight ratio of 40-60:15-30:5-20:0-20:4-6 and then granulated.
[0013] (3) Preparation of concrete road components
[0014] Add the solid waste-based rapid hardening cementitious material, iron tailings mixed sand, red mud-based lightweight aggregate, water and admixture obtained in step (1) at a ratio of 30-40:70-85:95-120:15-20:0.5-1, mix, pour into the mold, vibrate, demold, and cure to obtain the final product.
[0015] Furthermore, the solid waste-based rapid-hardening cementitious material comprises, by weight, 20-30 parts of slag powder, 15-25 parts of fly ash, 10-20 parts of gypsum, 5-15 parts of red mud, and 25-35 parts of high-efficiency binder.
[0016] The red mud-based lightweight aggregate, by weight, comprises: 40-60 parts red mud, 15-30 parts solid waste-based rapid-hardening cementitious material, 5-20 parts steel slag, 0-20 parts coal gangue, and 4-6 parts binder aqueous solution.
[0017] The concrete road components, by weight, include the following components: 340-400 parts of solid waste-based rapid-hardening cementitious material, 700-850 parts of iron tailings mixed sand, 950-1200 parts of red mud-based lightweight aggregate, 150-200 parts of water, and 5-10 parts of admixtures.
[0018] Furthermore, the slag powder is of grade S95 or higher, with a density ≥2.80 g / cm³. 3 Specific surface area ≥ 400 m² 2 / kg, moisture content ≤1.0%, conforming to the requirements of "Granulated Blast Furnace Slag Powder for Cement, Mortar and Concrete"; the fly ash is not lower than Grade II, density ≤2.50g / cm³. 3 Specific surface area ≥250m² 2 / kg, moisture content ≤1.0%, conforming to the requirements of "Fly Ash for Cement and Concrete"; the gypsum is preferably desulfurized gypsum with a density of 1.8~2.5g / cm³. 3 Specific surface area is 260–310 m² 2 / kg, dried moisture content ≤1.0%, in accordance with the requirements of "Industrial by-product gypsum used in cement".
[0019] Further, the preparation operation of the solid waste-based rapid-hardening cementitious material in step (1) is as follows:
[0020] S1. Mix, dry, and crush the wet red mud and gypsum materials. First, dry the red mud to reduce the moisture content to below 2.0% and set aside. Then, dry the gypsum to reduce the moisture content to below 1.0% and set aside. Dry the fly ash and slag powder and set aside.
[0021] S2. Mix water glass powder and high-strength clinker in a certain proportion to obtain a high-efficiency binder, and set aside.
[0022] S3. Add the aforementioned materials in the specified proportions and mix them by ball milling, controlling the specific surface area to be between 360 and 450 m². 2 / kg.
[0023] Furthermore, in step (1) S2, the mass ratio of high-strength clinker to water glass powder is 2:1 to 4:1, and the water glass modulus is 1.5 to 2.0.
[0024] Furthermore, the high-strength clinker is silicate cement clinker of grade not lower than 52.5.
[0025] Further, in step (1), the red mud used for preparing the solid waste-based rapid hardening cementitious material is Bayer process red mud with a particle size ≥100 mesh, a drying moisture content ≤2.0%, and a storage time ≥6 months; in step (2), the red mud used for preparing the red mud-based lightweight aggregate is Bayer process red mud, which is dried, crushed, dried, and ground to reduce the moisture content to 2.0% and the particle size passes through a 100 mesh sieve (≥100 mesh).
[0026] Furthermore, the 3d compressive strength of the solid waste-based rapid-hardening cementitious material is ≥42.5MPa, and the 3d flexural strength is ≥6.5MPa.
[0027] Further, the preparation of red mud-based lightweight aggregate in step (2) is as follows:
[0028] S1. Red mud concentrate is dried, crushed, dried, and ground for later use; coal gangue and steel slag concentrate is crushed, screened, dried, and ground for later use; solid waste-based rapid-hardening cementitious material is prepared for later use.
[0029] S2. Add the above materials in proportion, stir for 10-15 minutes, and let the powder age for 3-7 days.
[0030] S3, the cementitious agent aqueous solution is prepared and set aside;
[0031] S4. Add S2 powder material to S3 binder aqueous solution to granulate and form small spheres, and screen out spheres that meet the 5-20nm range.
[0032] S5. Qualified pellets are naturally cured at room temperature to the corresponding age, and then screened to obtain red mud-based lightweight aggregates with particle sizes of 5-10 nm and 10-20 nm.
[0033] Further, the steel slag in step (2) is converter steel slag, which is crushed, screened, dried and ground to reduce the moisture content to 1.0% and the particle size to pass through a 100-mesh sieve; the coal gangue is tunneling gangue, which is crushed, screened, dried and ground to reduce the moisture content to 1.0% and the particle size to pass through a 100-mesh sieve.
[0034] Further, the adhesive aqueous solution in step (2) is a paste-like adhesive prepared by mixing carboxymethyl cellulose or polyvinyl alcohol with water, and the mass ratio of adhesive to water is 0.1:100 to 0.5:100.
[0035] Furthermore, the adhesive aqueous solution should be prepared until there are no particulate objects in the solution and no solid-liquid separation phenomenon.
[0036] Further, the preparation of concrete road components in step (3) is as follows:
[0037] S1. Add solid waste-based rapid hardening cementitious material, iron tailings mixed sand and red mud-based lightweight aggregate in proportion, mix and vibrate, dry mix for 3-5 minutes, dilute the admixture with water to prepare an aqueous solution, add it slowly after the materials are evenly mixed, warm mix for 3-5 minutes to obtain red mud-based lightweight aggregate concrete.
[0038] S2. Pour the red mud-based lightweight aggregate concrete into the component mold while vibrating and pouring. After vibrating for 20-30 seconds, cure and finish the surface. Demold after the concrete reaches the required strength.
[0039] S3. After demolding, the red mud-based concrete road components are cured according to standard conditions at 1, 3, and 28 days. After reaching the curing period, performance testing and verification are carried out.
[0040] Furthermore, the iron tailings mixed sand mentioned in step (3) is a mixture of iron tailings sand and natural sand, with a mass ratio of iron tailings sand to natural sand of 1:1 to 3:1. After processing, it meets the "Standard for Quality and Inspection Methods of Sand and Stone for Ordinary Concrete".
[0041] Further, the additives mentioned in step (3) are water-reducing agents, antifreeze agents, and brighteners; the water-reducing agent is a polycarboxylate-based high-performance water-reducing agent, the antifreeze agent is a chloride salt rust-inhibiting antifreeze agent, and the brightener is a polymer-based brightener.
[0042] Furthermore, the water-reducing agent is added at 0.5% to 1.5% of the weight of the solid waste-based rapid-hardening cementitious material; the antifreeze agent is added at 0.5% to 1.5% of the weight of the solid waste-based rapid-hardening cementitious material; and the brightening agent is added at 0% to 1.0% of the weight of the solid waste-based rapid-hardening cementitious material.
[0043] The beneficial effects of this invention are:
[0044] 1. The solid waste-based cementitious material prepared in this invention utilizes the synergistic and mechanical activation effects of a rationally proportioned mixture of solid wastes such as red mud, desulfurized gypsum, fly ash, and slag powder to form hydraulic cementitious properties. Its mineral composition is similar to that of rapid-hardening sulfoaluminate cement, exhibiting excellent characteristics such as rapid hardening, early strength, and high strength. It can compensate for the shortcomings of ordinary silicate cement, significantly shorten the setting time, and improve the production efficiency of subsequent concrete component preparation. The preparation process does not require calcination, realizing the practical application value of large-scale industrial solid waste disposal, reducing environmental pollution and safety hazards.
[0045] 2. The red mud-based lightweight aggregate in this invention is a novel type of lightweight aggregate. It uses red mud, steel slag, and coal gangue as main raw materials, and replaces traditional cement with a solid waste-based rapid-hardening cementitious material. It is prepared using a non-sintering technology involving drying, grinding, granulation, curing, and screening. Compared with existing technologies requiring sintering, it has advantages such as high mechanical strength, a high proportion of solid waste, low investment cost, and low energy consumption. During the preparation of the red mud-based lightweight aggregate, the specially formulated solid waste-based rapid-hardening cementitious material of this invention, combined with a binder aqueous solution, helps the powder mixture to bond more quickly and rapidly generate cementitious properties, which helps to shorten the granulation time and improve the pelletizing efficiency of the red mud-based lightweight aggregate.
[0046] 3. The red mud-based lightweight aggregate prepared by the method of this invention has low density, high strength, good frost resistance, and excellent resistance to alkali-aggregate reaction, effectively solving the efflorescence phenomenon. Concrete road components made using this aggregate are lightweight, have high load-bearing capacity, and are low in cost. This not only achieves the effective utilization of solid waste such as red mud and conserves primary mineral resources, but also improves the performance and production efficiency of concrete road components, demonstrating good environmental benefits and promising market application prospects. Detailed Implementation
[0047] To clearly illustrate the technical features of this solution, the invention will be described in detail below through specific implementation methods.
[0048] Example 1
[0049] A red mud-based aggregate concrete road component, by weight, is prepared using the following components: 380 kg of solid waste-based rapid-hardening cementitious material, 800 kg of iron tailings mixed sand, 1100 kg of red mud-based lightweight aggregate, 160 kg of water, and 10 kg of admixture.
[0050] The aforementioned solid waste-based rapid-hardening cementitious material is made from the following components by weight, in a mass ratio of 10:15:15:25:25:38 kg of red mud, 57 kg of gypsum, 57 kg of fly ash, 95 kg of slag powder, and 133 kg of high-efficiency binder.
[0051] Among them, the iron tailings mixed sand is made of 400 kg of iron tailings sand and 400 kg of natural sand in a 1:1 mass ratio;
[0052] The red mud-based lightweight aggregate is made from the following components by weight: 550 kg of red mud, 275 kg of solid waste-based rapid-hardening cementitious material, 110 kg of steel slag, 110 kg of coal gangue, and 55 kg of binder aqueous solution.
[0053] The admixture, by mass ratio, consists of 4 kg of polycarboxylate-based high-performance water-reducing agent, 3 kg of chloride-based rust-inhibiting antifreeze agent, and 3 kg of polymer-based brightener; when using, add the aforementioned amounts of water to prepare an aqueous solution.
[0054] The preparation method of the above-mentioned red mud-based lightweight aggregate concrete road components is as follows:
[0055] Step 1: Preparation of solid waste-based rapid-hardening cementitious materials
[0056] S1. The wet materials of red mud and gypsum are turned, dried, and crushed. The red mud is first transported to the drying workshop to reduce the moisture content to below 2.0% and then stored in the red mud batching tank. The gypsum is then transported to the drying workshop to reduce the moisture content to below 1.0% and then stored in the gypsum batching tank. The dry materials of fly ash and slag powder are transported by tanker truck and pneumatic pump and stored in batching tanks respectively.
[0057] S2. Water glass powder and high-strength clinker are transported to the mixing workshop in a 1:3 ratio and stirred evenly to obtain a high-efficiency binder, which is then pumped to the binder mixing tank for storage using a pneumatic pump.
[0058] S3. Accurately add all materials from the mixing tank according to the specified proportions, and transport them to the grinding workshop for ball milling and mixing, controlling the specific surface area to 360-450 m². 2 / kg, stored in a finished product tank for solid waste-based rapid hardening cementitious materials.
[0059] Step 2: Preparation of Red Mud-Based Lightweight Aggregate
[0060] Red mud, coal gangue, steel slag, and solid waste-based rapid-hardening cementitious materials are added in proportion, mixed thoroughly for 15 minutes, and then stored in a powder tank for 7 days of aging. The binder is mixed with water to prepare a binder aqueous solution, which is then fully integrated and stored in a liquid tank. The powder material is fed into a disc granulator, and the binder aqueous solution is added evenly to gradually form granules. After molding, the granules are cured to the specified age and then screened to obtain red mud-based lightweight aggregate.
[0061] Step 3: The solid waste-based quick-hardening cementitious material, iron tailings mixed sand, and red mud-based lightweight aggregate are transported to a forced mixer for mixing according to the proportion. The mixing equipment is equipped with a CNC automatic concrete pouring and automatic vibration integrated system. Dry mix for 5 minutes, dilute the admixture with water to prepare an aqueous solution, and slowly add it after the mixture is evenly mixed. Wet mix for 5 minutes to obtain red mud-based lightweight aggregate concrete.
[0062] Step 4: Pour concrete material into various component molds, start vibration when it is half full, and continue vibrating while pouring. After vibrating for 30 seconds, transfer it to the curing area for finishing. After it has good strength, turn it over and automatically demold it to obtain red mud-based lightweight aggregate concrete road components.
[0063] Step 5: Place the concrete road components in a standard curing room for curing. The curing period is selected as 1 day, 3 days, or 28 days. After reaching the curing period, conduct tests and verifications on the road components for items such as appearance quality, dimensional deviation, mechanical properties, and physical properties.
[0064] Example 2
[0065] A red mud-based aggregate concrete road component is prepared by weight using the following components: 360 kg of solid waste-based rapid-hardening cementitious material, 720 kg of iron tailings mixed sand, 1200 kg of red mud-based lightweight aggregate, 162 kg of water, and 8 kg of admixture.
[0066] The aforementioned solid waste-based rapid-hardening cementitious material is made from the following components by weight: 36 kg of red mud, 54 kg of gypsum, 54 kg of fly ash, 90 kg of slag powder, and 126 kg of high-efficiency binder.
[0067] Among them, the iron tailings mixed sand is made of 480 kg of iron tailings sand and 240 kg of natural sand;
[0068] The red mud-based lightweight aggregate is made from 600 kg of red mud, 240 kg of solid waste-based rapid-hardening cementitious material, 60 kg of steel slag, 240 kg of coal gangue, and 60 kg of binder aqueous solution.
[0069] The additive consists of 3 kg of polycarboxylate-based high-performance water-reducing agent, 3 kg of chloride-based rust-inhibiting antifreeze agent, and 2 kg of polymer-based brightener. When using, add the aforementioned amounts of water to prepare an aqueous solution.
[0070] The preparation method of the above-mentioned red mud-based lightweight aggregate concrete road components is as follows:
[0071] Step 1: After drying, crushing and drying the red mud and gypsum wet materials, store them in the batching tank. Then, add the red mud, gypsum, fly ash, slag powder and high-efficiency binder dry materials in proportion, mix and grind them to obtain solid waste-based rapid hardening cementitious material.
[0072] Step 2: Preparation of Red Mud-Based Lightweight Aggregate
[0073] Red mud, coal gangue, steel slag, and solid waste-based rapid-hardening cementitious material are added in proportion, mixed thoroughly for 10 minutes, and then stored in a powder tank for 3 days of aging. The binder is mixed with water to prepare a binder aqueous solution, which is then fully integrated and stored in a liquid tank. The powder material is fed into a disc granulator, and the binder aqueous solution is added evenly to gradually form granules. After molding, the granules are cured to the specified age and then screened to obtain red mud-based lightweight aggregate.
[0074] Step 3: First, transport the solid waste-based quick-hardening cementitious material and iron tailings mixed sand to a forced mixer for mixing according to the proportion. The mixing equipment is equipped with a CNC automatic concrete pouring and automatic vibration integrated system. Dry mix for 5 minutes, then dilute the admixture with water to prepare an aqueous solution. After the mixture is evenly mixed, slowly add part of the aqueous solution and wet mix for 5 minutes. Finally, add the red mud-based lightweight aggregate and the remaining aqueous solution, and stir until uniform to obtain red mud-based lightweight aggregate concrete.
[0075] Step 4: Pour concrete material into various component molds, start vibration when it is half full, and continue vibrating while pouring. After vibrating for 30 seconds, transfer it to the curing area for finishing. After it has good strength, turn it over and automatically demold it to obtain red mud-based lightweight aggregate concrete road components.
[0076] Step 5: Place the concrete road components in a standard curing room for curing. The curing period is selected as 1 day, 3 days, or 28 days. After reaching the curing period, conduct tests and verifications on the road components for items such as appearance quality, dimensional deviation, mechanical properties, and physical properties.
[0077] Example 3
[0078] A red mud-based aggregate concrete road component is prepared by weight of the following components: 380 kg of solid waste-based rapid-hardening cementitious material, 850 kg of iron tailings mixed sand, 1040 kg of red mud-based lightweight aggregate, 174 kg of water, and 6 kg of admixture.
[0079] The solid waste-based rapid-hardening cementitious material is made from the following components by weight: 38 kg of red mud, 57 kg of gypsum, 57 kg of fly ash, 95 kg of slag powder, and 133 kg of high-efficiency binder.
[0080] Among them, the iron tailings mixed sand is made from 450 kg of iron tailings sand and 400 kg of natural sand;
[0081] The red mud-based lightweight aggregate is made from the following components by weight: 624 kg of red mud, 312 kg of solid waste-based rapid-hardening cementitious material, 52 kg of steel slag, and 52 kg of binder aqueous solution.
[0082] The admixture consists of 3 kg of polycarboxylate-based high-performance water-reducing agent and 3 kg of chloride-based rust-inhibiting antifreeze. When using, add the aforementioned amounts of water to prepare an aqueous solution.
[0083] The preparation method of the above-mentioned red mud-based lightweight aggregate concrete road components is as follows:
[0084] Step 1: After drying, crushing and drying the red mud and gypsum wet materials, store them in the batching tank. Then, add the red mud, gypsum, fly ash, slag powder and high-efficiency binder dry materials in proportion, mix and grind them to obtain solid waste-based rapid hardening cementitious material.
[0085] Step 2: Preparation of Red Mud-Based Lightweight Aggregate
[0086] Red mud, coal gangue, steel slag, and solid waste-based rapid-hardening cementitious materials are added in proportion, mixed thoroughly for 15 minutes, and then stored in a powder tank for 7 days of aging. The binder is mixed with water to prepare a binder aqueous solution, which is then fully integrated and stored in a liquid tank. The powder material is fed into a disc granulator, and the binder aqueous solution is added evenly to gradually form granules. After molding, the granules are cured to the specified age and then screened to obtain red mud-based lightweight aggregate.
[0087] Step 3: The solid waste-based quick-hardening cementitious material, iron tailings mixed sand, and red mud-based lightweight aggregate are transported to a forced mixer for mixing according to the proportion. The mixing equipment is equipped with a CNC automatic concrete pouring and automatic vibration integrated system. Dry mix for 5 minutes, dilute the admixture with water to prepare an aqueous solution, and slowly add it after the mixture is evenly mixed. Wet mix for 5 minutes to obtain red mud-based lightweight aggregate concrete.
[0088] Step 4: Pour concrete material into various component molds, start vibration when it is half full, and continue vibrating while pouring. After vibrating for 30 seconds, transfer it to the curing area for finishing. After it has good strength, turn it over and automatically demold it to obtain red mud-based lightweight aggregate concrete road components.
[0089] Step 5: Place the concrete road components in a standard curing room for curing. The curing period is selected as 1 day, 3 days, or 28 days. After reaching the curing period, conduct tests and verifications on the road components for items such as appearance quality, dimensional deviation, mechanical properties, and physical properties.
[0090] Comparative Example 1
[0091] The composition of this red mud-based lightweight aggregate concrete road component is the same as that in Example 1. The difference is that the solid waste-based rapid-hardening cementitious material used in the preparation of the component and the red mud-based lightweight aggregate is replaced with 42.5 rapid-hardening sulfoaluminate cement.
[0092] Comparative Example 2
[0093] The composition of this red mud-based lightweight aggregate concrete road component is the same as that in Example 1. The difference is that the solid waste-based rapid-hardening cementitious material used in the preparation of the component and the red mud-based lightweight aggregate is replaced with 42.5 ordinary Portland cement.
[0094] Comparative Example 3
[0095] The composition of this red mud-based lightweight aggregate concrete road component, by weight, includes the following components: 380 parts of solid waste-based rapid-hardening cementitious material, 760 parts of natural sand, 1100 parts of natural crushed stone, 190 parts of water, and 10 parts of admixture. The fine aggregate iron tailings mixed sand in Example 1 is replaced with natural sand, and the red mud-based lightweight aggregate is replaced with natural crushed stone; the rest of the preparation is the same as in Example 1.
[0096] Comparative Example 4
[0097] The composition of this red mud-based lightweight aggregate concrete road component is the same as in Example 1. The difference is in the preparation process of the red mud-based lightweight aggregate: red mud, coal gangue, steel slag, and solid waste-based rapid-hardening cementitious material are added in proportion, mixed thoroughly for 15 minutes, and then stored in a powder tank without aging treatment; the binder is mixed with water to prepare a binder aqueous solution, which is then fully integrated and stored in a liquid tank; the powder material is fed into a disc granulator, and the binder aqueous solution is added evenly to gradually form granules. The granules are then fed into a rotary kiln for calcination at a temperature of 1100℃~1200℃ for 10~20 minutes. As the rotary kiln rotates, the granules roll towards the kiln head. After exiting the kiln, they enter a cooler for cooling and are then screened to obtain the red mud-based lightweight aggregate.
[0098] Comparative Example 5
[0099] Conventional concrete road components, by weight, include the following components: 380 parts of 42.5 ordinary Portland cement, 760 parts of manufactured sand, 1100 parts of natural crushed stone, 190 parts of water, and 10 parts of admixtures.
[0100] The preparation methods for conventional concrete road components are as follows:
[0101] Step 1: 42.5 ordinary Portland cement, manufactured sand and natural crushed stone are transported to a forced mixer for mixing according to the proportion. The mixing equipment is equipped with a CNC automatic concrete pouring and automatic vibration integrated system. Dry mix for 5 minutes, dilute the admixture with water to prepare an aqueous solution, and slowly add it after the mixture is evenly mixed. Wet mix for 5 minutes to obtain ordinary concrete material.
[0102] Step 2: Pour concrete material into various component molds, start vibration when it is half full, and continue vibrating while pouring. After vibrating for 30 seconds, transfer it to the curing area for finishing. After it has good strength, turn it over and automatically demold it to obtain ordinary concrete road components.
[0103] Step 3: Place the road components in a standard curing room for curing, with curing periods of 1 day or 28 days. After reaching the curing period, conduct tests and verifications on the road components for appearance quality, dimensional deviation, mechanical properties, and physical properties.
[0104] Comparative Example 6
[0105] The composition of the red mud-based lightweight aggregate concrete road component is the same as that in Example 1, except that the solid waste-based rapid-hardening cementitious material is replaced by a red mud-based cementitious material prepared with the following mass percentage components: 20% red mud, 27% mineral powder, 9% gypsum, and 44% ordinary binder. The ordinary binder is prepared by mixing ordinary grade cement and sodium silicate in a mass ratio of 3:1 and is in solid powder form.
[0106] Comparative Example 7
[0107] The composition of this red mud-based lightweight aggregate concrete road component is the same as in Example 1, except that the amount of red mud in both the solid waste-based rapid-hardening cementitious material and the red mud-based lightweight aggregate is increased, as detailed below:
[0108] The solid waste-based rapid-hardening cementitious material is composed of the following weight composition: 40 kg of red mud, 10 kg of gypsum, 20 kg of slag powder, 10 kg of fly ash, and 20 kg of binder.
[0109] The weight composition of the red mud-based lightweight aggregate is as follows: 660 kg of red mud, 275 kg of solid waste-based rapid-hardening cementitious material, 55 kg of steel slag, 55 kg of coal gangue, and 55 kg of binder aqueous solution.
[0110] Performance tests were conducted on the examples and comparative examples according to the "Sulfoaluminate Cement", "Lightweight Aggregates and Their Test Methods", and "Technical Guidelines for Precasting and Installation of Small Cement Concrete Components for Highways".
[0111] I. The solid waste-based cementitious materials prepared in the examples and the 42.5 rapid-hardening sulfoaluminate cement and 42.5 ordinary Portland cement used in the comparative examples were tested. The test results are shown in Table 1 below:
[0112] Table 1. Test results of cementitious material properties
[0113]
[0114] As shown in Table 1, the solid waste-based rapid-hardening cementitious material prepared by the method of this invention uses industrial solid wastes such as red mud, fly ash, and gypsum as raw materials. It is utilized through non-calcination technologies such as precipitation drying and grinding mixing. It has excellent properties such as early strength, high strength, and rapid hardening. The 3-day compressive strength is 45.6 MPa and the 3-day flexural strength is 8.0 MPa. The technical indicators meet the 42.5 rapid-hardening sulfoaluminate cement standard and are superior to the 42.5 ordinary Portland cement standard.
[0115] II. The performance of concrete road components prepared in each embodiment and comparative example was tested, and the test results are shown in Table 2 below.
[0116] Table 2 Performance test results of concrete road components
[0117]
[0118] As shown in Table 2, Comparative Example 1 and Example 1 of the present invention have the same mix proportion but different cementitious materials. The concrete components prepared by both have similar performance, but the cost of the solid waste-based rapid-hardening cementitious material is significantly reduced. Rapid-hardening sulfoaluminate cement is a special type of cement, priced at 800-1000 yuan, and has a low cost-performance ratio. The solid waste-based rapid-hardening cementitious material developed in this invention has a similar mineral composition and technical performance to rapid-hardening sulfoaluminate cement, and can perfectly replace it.
[0119] Compared with Example 1, Comparative Example 2 has the same mix ratio but different cementitious materials. The concrete components prepared with ordinary Portland cement set slowly and could not reach the C30 grade strength in a short time. The solid waste-based rapid-hardening cementitious material of the present invention is similar in price to ordinary Portland cement and has excellent properties such as early strength, high strength and rapid hardening. It can significantly shorten the concrete setting time and improve the production efficiency of components.
[0120] Compared with Example 1, Comparative Example 3 has the same mix proportion but different aggregates. It completely replaces natural crushed stone and natural sand with red mud-based lightweight aggregate and tailings sand. The concrete components prepared by the two are similar in performance. However, red mud-based lightweight aggregate and tailings sand not only save a lot of natural mineral and rock resources, but also significantly reduce production costs. The red mud-based lightweight aggregate particles are spherical, and the workability of the prepared concrete mixture is good, which is beneficial to construction operations.
[0121] Compared with Example 1, Comparative Example 4 has the same mix ratio but a different preparation process for red mud-based lightweight aggregate. The concrete components prepared using the fully non-calcining technology of the present invention have slightly better performance than those prepared using the calcining technology. The non-calcining preparation step in the method of the present invention has advantages such as high mechanical strength, high solid waste ratio, low investment cost, and low energy consumption. The strength of the non-calcined lightweight aggregate also increases with age due to the synergistic reinforcement between components, thereby improving the concrete strength and its mechanical properties.
[0122] Compared with Example 1, the concrete component prepared by the solid waste-based rapid-hardening cementitious material in Comparative Example 5 only needs 1 day to reach the C30 grade of compressive strength and 28 days to reach the C50 grade of compressive strength. It is superior to conventional concrete components in terms of setting time and mechanical strength.
[0123] Compared with Example 1, the composition of the solid waste-based rapid-hardening cementitious material in Comparative Example 6 was changed. It used a different solid waste-based rapid-hardening cementitious material than the one mentioned in the method of this invention. Compared with this invention, the strength of the component was reduced and the demolding time was increased. This shows that although the raw materials are roughly the same, slight adjustments to the material ratio will have a certain impact on the performance of the cementitious material and the component.
[0124] Compared with Example 1, Comparative Example 7 showed an increase in the amount of red mud used in both solid waste-based rapid-hardening cementitious materials and red mud-based lightweight aggregates. Based on the increased utilization of red mud solid waste, the performance of the components was examined and it was found that although the utilization of red mud was increased, the impact on the appearance quality and mechanical properties of the products indirectly reflected the reduced utilization efficiency of red mud in actual production applications.
[0125] The above specific embodiments should not be construed as limiting the scope of protection of the present invention. For those skilled in the art, any alternative improvements or modifications made to the embodiments of the present invention shall fall within the scope of protection of the present invention.
[0126] Any aspects of this invention not described in detail are well-known to those skilled in the art.
Claims
1. A method for preparing concrete road components using a novel red mud-based aggregate, characterized in that, The following steps are included: (1) Preparation of solid waste-based rapid hardening cementitious materials Red mud, gypsum, fly ash, slag powder, and high-efficiency binder are added in a weight ratio of 5~15:10~20:15~25:20~30:25~35 and mixed by ball milling; the preparation operation is as follows: S1. Mix, dry, and crush the wet red mud and gypsum materials. First, dry the red mud to reduce the moisture content to below 2.0% and set aside. Then, dry the gypsum to reduce the moisture content to below 1.0% and set aside. Dry the fly ash and slag powder and set aside. S2. Mix the high-strength clinker and water glass powder at a mass ratio of 2:1 to 4:1 to obtain the high-efficiency binder, and set aside. S3. Add the aforementioned materials in the specified proportions and mix them by ball milling, controlling the specific surface area to be 360~450 m². 2 / kg; (2) Preparation of red mud-based lightweight aggregate Red mud, solid waste-based rapid-hardening cementitious material, steel slag, coal gangue, and binder aqueous solution are added at a weight ratio of 40~60:15~30:5~20:0~20:4~6, and granulated. The preparation operation is as follows: S1. Red mud concentrate is dried, crushed, dried and ground for later use; coal gangue and steel slag concentrate are crushed, screened, dried and ground for later use; solid waste-based rapid hardening cementitious material prepared in step (1) is prepared for later use. S2. Add the above materials in proportion, stir for 10-15 minutes, and age the powder for 3-7 days. S3, the adhesive aqueous solution is prepared and set aside; S4. Add the S2 powder material from step (2) to the S3 binder aqueous solution from step (2) to granulate and form small spheres. Screen the spheres that meet the requirements of 5~20nm and discharge them. S5. Qualified pellets are naturally cured at room temperature to the corresponding age, and then screened to obtain red mud-based lightweight aggregates with particle sizes of 5~10nm and 10~20nm. (3) Preparation of concrete road components Add the solid waste-based rapid hardening cementitious material, iron tailings mixed sand, red mud-based lightweight aggregate, water and admixture obtained in step (1) at a weight ratio of 30~40:70~85:95~120:15~20:0.5~1, mix, inject into the mold, vibrate, demold, and cure to obtain the final product.
2. The method for preparing concrete road components using red mud-based novel aggregates according to claim 1, characterized in that, Step (3) The preparation of concrete road components is as follows: S1. Add solid waste-based rapid hardening cementitious material, iron tailings mixed sand and red mud-based lightweight aggregate in proportion, mix and vibrate, dry mix for 3-5 minutes, dilute the admixture with water to prepare an aqueous solution, add it slowly after the materials are evenly mixed, warm mix for 3-5 minutes to obtain red mud-based lightweight aggregate concrete. S2. Pour the red mud-based lightweight aggregate concrete into the component mold while vibrating and pouring. After vibrating for 20-30 seconds, cure and finish the surface. Demold after the concrete reaches the required strength. S3. After demolding, the red mud-based concrete road components are cured according to standard conditions at 1, 3, and 28 days. After reaching the curing period, performance testing and verification are carried out.
3. The method for preparing concrete road components using red mud-based novel aggregates according to claim 1, characterized in that, The adhesive aqueous solution in step (2) is a paste-like adhesive prepared by mixing carboxymethyl cellulose or polyvinyl alcohol with water, and the mass ratio of adhesive to water is 0.1:100~0.5:
100.
4. The method for preparing concrete road components using red mud-based novel aggregates according to claim 1, characterized in that, The iron tailings mixed sand mentioned in step (3) is a mixture of iron tailings sand and natural sand, with a mass ratio of iron tailings sand to natural sand of 1:1 to 3:
1.
5. The method for preparing concrete road components using novel red mud-based aggregates according to claim 1, characterized in that, The additives in step (3) are water-reducing agents, antifreeze agents, and / or brighteners; the water-reducing agent is a polycarboxylate-based high-performance water-reducing agent, the antifreeze agent is a chloride salt rust-inhibiting antifreeze agent, and the brightener is a polymer-based brightener.
Citation Information
Patent Citations
Red mud-based ceramsite concrete and preparation method and application thereof
CN111302746A
Red mud unfired aggregate
CN114455868A
Unfired magnetic ceramsite prepared from steel slag and red mud compounded mining and metallurgy solid waste as well as preparation method and application of unfired magnetic ceramsite
CN116496029A
Red-mud-based high-performance concrete curb and preparation method thereof
CN117185767A